Gorlin syndrome: A case report - Patil K; Mahima V; Gupta B (Wolters Kluwer Medknow Publications, 2005)
Gorlin syndrome is an autosomal dominant inherited condition that exhibits high penetrance and variable expressivity. It is characterized mainly by Basal cell carcinomas, Odontogenic keratocysts and skeletal anomalies. However, medical literature documents both common and lesser known manifestations of the disorder involving the skin, central nervous system, skeletal system etc. Diagnosis of the syndrome in childhood is basically through oral abnormalities. A case of Gorlin syndrome has been reported here, with review of literature.